ANALISIS CITRA PEWARNA ALAMI DARI EKSTRAK KULIT BUAH NAGA (Hylocereus polyrhizus) - Hidayah, Noor; Aji, Mahardika Prasetya; Sulhadi, Sulhadi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
The dragon fruits are a similar plant in Indonesia. It has thick peel. The peel of dragon fruit has less benefit. The peel of dragon fruit contains anthocyanin pigment which gives red color. The super red dragon fruit ((Hylocereus polyrhizus) are used in this research. The extraction of anthocyanin are taken by boiling dragon fruit with water; it will continue until the change to the red fluid. The next experiment, the fabric is immersed in it. The quality of fabric is showed from Intensity Black and White value, in this experiment, the fluid extraction is added with water. If the composition of extraction are added more then the value of Intensity Black and White are increased. The goal of the research is to get best of color for fabric, So the ratio of fluid extraction and water is 2:1. It should change fabric color to pink. Keywords: peel of dragon fruit, extraction, color.